The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1590/s1677-5538.ibju.2023.0558
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of mapping-targeted biopsies on the index lesion in transperineal prostate biopsies

Nahuel Paesano,
Violeta Catalá,
Larisa Tcholakian
et al.

Abstract: Purpose: To evaluate the eff ectiveness of mapping-targeted biopsies (MTB) on the index lesion for the detection of clinically significant prostate cancer (csPCa) in transperineal fusion-image prostate biopsies. Materials and Methods:A retrospective analysis was conducted on 309 men with suspected PCa who underwent prostate biopsies at the Creu Blanca reference center in Barcelona, Spain. The Prostate Imaging-Reporting and Data System (PI-RADS v.2.1) of the magnetic resonance images (MRI) were reclassified by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Dr. Paesano and collegues from Spain, performed in page 296 ( 4 ) a nice study about the effectiveness of mapping-targeted biopsies on the index lesion in transperineal prostate biopsies and concluded that this model had the potential to avoid 23.3% of prostate biopsies without missing additional csPCa cases. Mapping-targeted biopsies of the index lesion was highly effective for identifying clinically significant prostate cancer (csPCa) in fusion transperineal prostate biopsies.…”
mentioning
confidence: 99%
“…Dr. Paesano and collegues from Spain, performed in page 296 ( 4 ) a nice study about the effectiveness of mapping-targeted biopsies on the index lesion in transperineal prostate biopsies and concluded that this model had the potential to avoid 23.3% of prostate biopsies without missing additional csPCa cases. Mapping-targeted biopsies of the index lesion was highly effective for identifying clinically significant prostate cancer (csPCa) in fusion transperineal prostate biopsies.…”
mentioning
confidence: 99%